Exploring best soil conservation practices using the tolerable soil loss limit in central highland of Ethiopia: A case study of Andit Tid watershed - Abebe, Tilahun Getachew; Lemma, Tesfaye Mebrate; Meshesha, Tesfa Worku (International Soil and Water Conservation Research, 2025)
Soil erosion is a major issue in Ethiopia, prompting ongoing watershed development campaigns. This study contributes to exploring Best Soil Conservation practices (BSCPs) to reduce erosion rates to/or below Tolerable Soil Loss Limits (TSLLs). To achieve these the study used the SWAT model, coupled with the SWAT Calibration and Uncertainty Procedures (SWAT-CUP), for simulation, sensitivity analysis, calibration, and validation using streamflow and sediment yield data. The calibrated SWAT model was used to assess soil erosion hotspot areas and evaluate the effectiveness of the selected BSCPs: Soil and/or Stone Bund (SSB), Grass strip (GT), reforestation (RF), Soil and/or Stone Bund and grass strip (SSB and GT) and Soil and/or Stone Bund and Reforestation (SSB and RF). The results revealed that 22.9% of the area showed soil loss rates below the TSLL. Furthermore, varying degrees of erosion above the TSLL was observed, with sub-watershed SW-12 experiencing the highest erosion rate (47 t ha−1yr−1) and sub-watershed SW-2 experiencing the lowest (7.8 t ha−1yr−1). Among the evaluated BSCPs, SSB + RF demonstrated the greatest erosion reduction effectiveness at 76.6%, followed by SSB + GT, SSB, RF, and GT, with erosion reduction effectiveness values of 61.7%, 60.0%, 43.3%, and 13.9%, respectively. Based on these findings, SSB + RF is recommended for erosion reduction to or below the TSLL, with implementation priority given to sub-watersheds SW-12, SW-10, SW-3, SW-2, and SW-5, ranked in descending order of erosion rate severity. During implementation, emphasis should be placed on reforestation of plant species of high ecological importance.